Subject-oriented business process management Second international conference, S-BPM ONE 2010, Karlsruhe, Germany, October 14, 2010. Selected papers - Schmidt, Werner; Singer, Robert; Seese, Detlef (Communications in Computer and Information Science, 2011)
This book constitutes the thoroughly refereed post-proceedings of the Second International Conference on Subject-Oriented Business Process Management, S-BPM ONE 2010, held in Karlruhe, Germany.